Lamb - Hnizdovsky, Jacques ([S. l.] : [s. n.], 1974)
Prikaz janjeta.
Signatura autora ispod otiska olovkom: Hnizdovsky // Lamb 1974 85/150.
Digitalna reprodukcija
Hnizdovsky : Woodcuts, 1944-1975. Gretna : Pelican Publishing Company, 1976.
Keywords: Drvorezi